The complete Carbon programming course - Percival, Rob (Packt Publishing, 2024)
Embark on a comprehensive journey through the Carbon programming language with this meticulously structured course. Starting with the basics, you'll delve into variables, data types, and output, progressing through operators, tuples, and pointers. Each section builds upon the previous one, ensuring a seamless and thorough understanding of Carbon's foundational elements. As you advance, you'll explore control statements and arrays, gaining proficiency in selection and repetition control statements. Practical projects are integrated to solidify your learning, allowing you to apply theoretical knowledge to real-world scenarios. The course's emphasis on hands-on practice ensures you develop not just theoretical understanding but also practical coding skills. The final sections introduce you to the intricacies of functions and object-oriented programming (OOP). You'll learn about classes, inheritance, polymorphism, and abstract classes, culminating in a comprehensive project that consolidates all the skills acquired throughout the course. By the end, you'll be well-equipped to tackle complex programming challenges using Carbon, setting a strong foundation for your programming career.
Online resource; title from title details screen (O'Reilly, viewed August 19, 2024)
Keywords: Object-oriented programs (Computer programs); Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet